2020
DOI: 10.3133/sim3464
|View full text |Cite
|
Sign up to set email alerts
|

Geologic map of Jezero crater and the Nili Planum region, Mars

Abstract: For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U.S. Government. Although this information product, for the most part, is in the public domain, it also may contain copyrighted materials as noted in the text. Permission to reproduce copyrighted items must be secured from the copyright owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 36 publications
3
70
0
1
Order By: Relevance
“…The ROB unit has a fractured, rubbly, and often ridged morphology outside of Jezero crater, which resembles margin fractured and CFF 2 unit rocks inside of Jezero crater (Figure 16). As described in Section 4.3.2, the ROB unit drapes into Jezero crater and transitions into the margin fractured unit with no clear contacts, implying that they are likely the same unit, as past photogeologic mapping has also indicated (Goudge et al., 2015; Sun & Stack, 2020). The thermal inertia values of carbonate‐bearing rocks in the ROB unit outside of Jezero crater cover a range that encompasses the thermal inertia values of carbonate‐bearing rocks inside of Jezero crater (Figure 17).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The ROB unit has a fractured, rubbly, and often ridged morphology outside of Jezero crater, which resembles margin fractured and CFF 2 unit rocks inside of Jezero crater (Figure 16). As described in Section 4.3.2, the ROB unit drapes into Jezero crater and transitions into the margin fractured unit with no clear contacts, implying that they are likely the same unit, as past photogeologic mapping has also indicated (Goudge et al., 2015; Sun & Stack, 2020). The thermal inertia values of carbonate‐bearing rocks in the ROB unit outside of Jezero crater cover a range that encompasses the thermal inertia values of carbonate‐bearing rocks inside of Jezero crater (Figure 17).…”
Section: Resultsmentioning
confidence: 83%
“…Non‐deltaic carbonate‐bearing rocks within Jezero crater resemble the ROB unit in every metric that is observable from orbit, including VNIR spectral properties, morphology, thermal inertia, and thickness given observations of the ROB unit in Libya Montes. The ROB unit also drapes into Jezero crater, directly connecting to the margin fractured unit with no visible contacts (Sun & Stack, 2020). It is therefore unlikely that these practically identical rock units were deposited and altered by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date include one early field study by a small team representing various instruments (Martin et al 2020), an exercise on a "mystery rock" within the SuperCam team (Ollila et al 2019), and several remote operations and science team training (ROASTT) events organized within the Mars 2020 project (Lawson et al, in preparation). All of these were much more limited in scope than is expected to be experienced with the Perseverance rover covering multiple outcrops over a large field area (Sun and Stack 2020). We expect the synergy experienced at both the human level, and with tools such as machine learning, will provide surprising discoveries that would not be possible without combining the results of the individual techniques.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…There are a variety of depositional mechanisms proposed for the Cf-fr unit; igneous (e.g., Goudge et al, 2012Goudge et al, , 2015Schon et al, 2012) as well as fluvial or aeolian sedimentary (Kah et al, 2020;Stack et al, 2020). Several authors (e.g., Goudge et al, 2015;Horgan et al, 2020;Sun & Stack, 2020b) have suggested a potential correlation between the crater floor unit and a unit mapped outside of the crater, the Sun and Stack (2020b) Nili plains 2 unit and Bramble et al's (2017) mafic capping unit. If the Cf-fr unit is related to the geographically widespread Nili Planum capping unit (see also Hundal et al, 2020;Sun & Stack, 2020a, 2020b, the unit spans too large a range in elevation for a volcanic flow to be a viable emplacement mechanism, whereas airfall deposition could explain the range in elevation (Sun & Stack, 2020a, 2020b.…”
Section: Crater Floor Fractured Roughmentioning
confidence: 99%
“…Figure modified after Stack et al (2020). Us unit extent after Sun and Stack (2020b). (b-d) Surface expression of the Cf-f-1, Cf-fr, and Us units in Jezero crater.…”
Section: Introductionmentioning
confidence: 99%